Identification of E-business solution to support key business processes within the existing business. Based on ‘Bogatyr Trans’ Ltd case study. - Kuspekova, Karlygash (2011)
The E-business last decades experiences a phenomenal grown and in this respect more and more enterprises transform their business from traditional one. At the same time this has gave a push to the development of different e-business approaches and solutions. Choice, and subsequently implementation of e-business solution becomes an important aspect of the transaction from traditional business. The choice of the solution depends on the specific of business process, activities involving within process and also relationship among participates. In addition the process of choice involves determination and rethinks organizations‟ reality, strategy, processes, and then itself the process of implementation. The aim of this research is to investigation of procurement process of Bogatyr Trans, Ltd in order to identify potential e-business solution which is appropriate to this process. To accomplish the aim as a theoretical framework of the dissertation the Krell and Gale transactional model was used to examine existing procurement process, to set potential e-enable activities and subsequently determination of suitable e-business solution. Before proceeding with consideration of Bogatyr Trans, Ltd. there was examination of E-Business, its applications and technologies, and also the study about organizational changes as part of e-business implementation process and transactions model took a part. The basic component of the dissertation is on a single case study with a single –unit analyses drawn upon the primary and secondary data analysis. The result of the case study research shows that e-reverse auction solution better suits for procurement process of Bogatyr Trans, Ltd. Another important finding was that by taking into account specific of the process there was also suggested to implement Web-Based ERP system. Finally, there were recommended that when selecting e-business solution provider should take into account the specificity of business of Bogatyr Trans. It was also recommended provide simultaneous implementation of Web-based ERP and e-reveres auction solution. The recommendations related to change management include creation of clear implementation plan, organise project team, and also provide stuff training.